Extreme drought causes fish recruitment failure in a fragmented Great Plains riverscape. Issue 6 (28th June 2019) - Perkin, Joshuah S.; Starks, Trevor A.; Pennock, Casey A.; Gido, Keith B.; Hopper, Garrett W.; Hedden, Skyler C.
Abstract: Dryland stream fishes are adapted to highly connected habitats with unpredictable hydrologic conditions, including frequent low flows and sometimes extreme drought. The low flow recruitment hypothesis predicts that some fishes spawn in main channel habitats during low flows when water temperatures and prey densities are high. However, extreme low flows during drought periods might be disruptive even among fishes whose life histories otherwise benefit from lower flows. We studied recruitment dynamics of six fishes (family Cyprinidae) at 15 sites in a fragmented Great Plains riverscape in Kansas, USA, during 2 years of extreme drought. We tracked the chronology of gonadal development and age 0 recruitment to test the hypothesis that recruitment by fishes that broadcast spawn planktonic ova would be less successful compared with fishes that spawn demersal or adhesive ova. We found all six taxa were reproductively active but recruitment was evident for only four. The two species for which recruitment was not evident, peppered chub ( Macrhybopsis tetranema ) and silver chub ( Macrhybopsis storeriana ), are confirmed or suspected pelagic‐broadcast spawning fishes that have declined in other fragmented and dewatered Great Plains riverscapes. Our data highlight the potential for extreme low flows within isolated stream fragments to cause complete or near‐complete recruitment failure for pelagic‐broadcast spawning fishes, especially those with small population sizes. Failed recruitment during extreme drought may be related to spawning mode, ova characteristics, or both. Our work informs management of fish diversity in drought‐prone riverscapes by establishing mechanistic linkages among extreme drought, fish recruitment, and assemblage structure.